ADVOKASI WARTAWAN KORBAN KEKERASAN DI ALIANSI JURNALIS INDEPENDEN MALANG - Suhardi; Qorib, Fathul (Unitri Press, 2019)
Communication patterns occur in every organization, including the Alliance of Independent Journalists/Aliansi Jurnalis Independen (AJI) Malang in advocating journalists. Journalists who are members of AJI Malang will find it easier to overcome problems while carrying out their journalistic tasks because AJI Malang has three main issues that are always the center of attention, which are the struggle to maintain press freedom, improve journalist's professionalism, and improve the welfare of journalists. The purpose of this study was to determine the organizational communication pattern of the Alliance of Independent Journalists (AJI) Malang in advocating journalists and factors that hinder the Malang Alliance of Independent Journalists (AJI) in advocating journalists. This study used qualitative research methods. The method of data analysis used by researchers is the descriptive method, which describes the results of the data obtained.The results of the study prove that the communication pattern of the Alliance of Independent Journalists (AJI) Malang uses the primary, secondary, linear and circular communication patterns. While the factors that hinder the Malang Alliance of Independent Journalists (AJI) in advocating for journalists are two factors, which are the internal factor comes from the number of journalists who have not understood the journalistic code of ethics and stopped the case in the middle of an advocacy process. While external factors came from press companies that were less proactive in guarding advocacy by journalists.